Complex Surgical Treatment in A Patient with Locally Extended Rinosinusal Cancer - Case Report (Archives of Clinical and Medical Case Reports, 2023)
Introduction: Sinonasal malignancies are one of the rarest pathologies encountered in the ENT clinical field, less than 5% of all head and neck cancers. Endoscopic approach for all types of surgical pathologies has become the preferred method however, the external or combined approach is still necessary in selected cases. Surgical approach of the mid-structure of the face should always be performed with a reconstructive plan in mind. As presented in a multitude of studies, head and neck cancer survivors, especially the ones that underwent surgery, have a difficult time adjusting to their new condition, rejoin society, return to work and overall have a lower quality of life. Material and method: This case report was based on following a patient admitted in the ENT Clinic of “Coltea” Clinical Hospital, from diagnosis to treatment and follow-up. Patient consent was taken for all photographs and imaging used in this article. Results: Patient presented in the clinic with a tumoral growth on the right part of the nose, complaining of nasal obstruction, facial deformity and a few episodes of anterior epistaxis that stopped spontaneously. A tumour resection was performed but the disease reappeared in 6 months, requiring re-intervention of a greater calibre, with a complex reconstruction of the maxillo-facial structures. Conclusion: 1. Rinosinusal carcinoma is a rare condition,